IЧ спектри н-пентанолу і н-октанолу в рiдкому i твердому станах - Vasylieva, A.; Doroshenko, I.; Pogorelov, V.; Sablinskas, V.; Balevicius, V. (Publishing house "Academperiodika", 2019)
Alcohol molecules can form hydrogen bonds and arrange in different structures named clusters. The aim of this work is to study the behavior of a cluster structure of alcohols at phase transitions and to elucidate the structure of clusters in the solid and liquid states.The objects of investigation are monohydric alcohols n-pentanol (CH2)4CH3–OH and n-octanol (CH2)7CH3–OH. For the structural analysis of the clusters, the matrix isolation FTIR spectroscopy is used, while the spectroscopic studies of the behavior of different clusters at the solid-liquid phase transition are performed in the liquid and solid states. In order to interpret the experimental spectra, the quantum-chemical calculations with the use of Gaussian03 software (approximation DFT/B3LYP, 6–31G (d, p) are carried out.